2022
DOI: 10.21203/rs.3.rs-1844677/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 S1 Protein Persistence in SARS-CoV-2 Negative Post-Vaccination Individuals with Long COVID/ PASC-Like Symptoms

Abstract: Background We sought to determine the immunologic abnormalities in patients following SARS-CoV-2 vaccines who experience post-acute sequelae of COVID-19 (PASC)-like symptoms > 4 weeks post vaccination. In addition, we investigated whether the potential etiology was similar to PASC. Design: We enrolled 50 post-vaccination individuals who experience PASC-like symptoms, 10 healthy individuals, and 35 individuals post-vaccination without symptoms. We performed multiplex cytokine/chemokine profiling with machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…A follow-on preprint study involved individuals who experienced PASC-like symptoms post vaccination for COVID-19. CD16+ monocytes were isolated from six of these patients, and it was confirmed that they too contained both S1 and S2 sequences, as well as several mutant S1 peptides [42]. It was proposed that the continual release of spike protein fragments from these monocytes could be sustaining the PASC symptoms.…”
Section: Cd16+ Monocytes and Toll Like Receptormentioning
confidence: 83%
“…A follow-on preprint study involved individuals who experienced PASC-like symptoms post vaccination for COVID-19. CD16+ monocytes were isolated from six of these patients, and it was confirmed that they too contained both S1 and S2 sequences, as well as several mutant S1 peptides [42]. It was proposed that the continual release of spike protein fragments from these monocytes could be sustaining the PASC symptoms.…”
Section: Cd16+ Monocytes and Toll Like Receptormentioning
confidence: 83%
“…However, evidence of integration of non-retroviral subgenomic viral RNA into the host cell has been described for some viruses, such as Ebola virus, Marburg virus [54] , vesicular stomatitis virus and lymphocytic choriomeningitis virus [55] , [56] , [57] in humans and other mammalian hosts [58] , and it is now thought that human retrotransposons can facilitate reverse transcription of non-retroviral viral RNA genomes and, subsequently, enable their genomic insertion [56] . SARS-CoV-2 RNA has been detected for months in many recovered COVID-19 patients that were not shedding infectious virus, and a pre-print of a study that followed a cohort of 50 individuals that were exhibiting symptoms of long-COVID post vaccination, reported a similar finding [59] . A proposed explanation of this phenomenon was that parts of the SARS-CoV-2 genome could be undergoing reverse-transcription and genomic integration within infected somatic cells, leading to persistent transcription of the integrated sequences.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 80%
“…Independent research has shown that a higher number of doses of the injectables is actually associated with a greater likelihood of hospitalization, diagnosis of COVID disease, and death following the diagnosis (Gazit et al, 2021;Brown et al, 2021;Seneff & Nigh, 2021;Classen, 2021;Berdine, 2022). Moreover, increasingly it has become clear that persons with "long COVID" are more apt to have received one or more of the COVID-19 injections than not (Patterson et al, 2022) and there is pervasive clinical evidence that the COVID-19 vaccine based spike protein can cause disease and even death by itself (Bansal et al, 2021).…”
Section: The Mainstream Narrative Depends On a Biological Liementioning
confidence: 99%